Engineering the Mechanics of Heterogeneous Soft Crystals. (12th August 2016) - Cho, Hansohl; Weaver, James C.; Pöselt, Elmar; in't Veld, Pieter J.; Boyce, Mary C.; Rutledge, Gregory C.
Abstract : This work demonstrates how the geometric and topological characteristics of substructures within heterogeneous materials can be employed to tailor the mechanical responses of soft crystals under large strains. The large deformation mechanical behaviors of elastomeric composites possessing long‐range crystalline order are examined using both experiments on 3D‐printed prototype materials and precisely matched numerical simulations. The deformation mechanisms at small and large strains are elucidated for six sets of morphologies: dispersed particles on each of the simple cubic, body‐centered cubic or face‐centered cubic lattices, and their bi‐continuous counterparts. Comparison of results for the six types of morphologies reveals that the topological connectivity of dissimilar domains is of critical importance for tailoring the macroscopic mechanical properties and the mechanical anisotropy. Abstract : Tailoring the mechanical responses of soft crystals under large strains by employing the geometric characteristics is demonstrated. The large deformation mechanical behaviors of elastomeric composites possessing long‐range crystalline order are examined using both experiments and numerical simulations. The results revealed that the topological connectivity of dissimilar domains is of critical importance for tailoring the macroscopic mechanical properties and the mechanical anisotropy.